Phytochemical profile of brown rice and its nutrigenomic implications - Keneswary Ravichanthiran; Zheng, Feei Ma; Hongxia Zhang; Yang Cao; Chee Woon Wang; Shahzad Muhammad; Elom K. Aglago; Yihe Zhang; Yifan Jin; Binyu Pan (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Whole grain foods have been promoted to be included as one of the important components of a healthy diet because of the relationship between the regular consumption of whole-grain foods and reduced risk of chronic diseases. Rice is a staple food, which has been widely consumed for centuries by many Asian countries. Studies have suggested that brown rice is associated with a wide spectrum of nutrigenomic implications such as anti-diabetic, anti-cholesterol, cardioprotective and antioxidant. This is because of the presence of various phytochemicals that are mainly located in bran layers of brown rice. Therefore, this paper is a review of publications that focuses on the bioactive compounds and nutrigenomic implications of brown rice. Although current evidence supports the fact that the consumption of brown rice is beneficial for health, these studies are heterogeneous in terms of their brown rice samples used and population groups, which cause the evaluation to be difficult. Future clinical studies should focus on the screening of individual bioactive compounds in brown rice with reference to their nutrigenomic implications.